2000
DOI: 10.1128/jcm.38.10.3815-3821.2000
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Entamoeba spp.: Evidence of a Bottleneck (Demographic Sweep) and Transcontinental Spread of Diploid Parasites

Abstract: Entamoeba histolytica causes amebic colitis and liver abscess in developing countries such as Mexico and India.Entamoeba dispar is morphologically identical but is not associated with disease. Here we determined the ploidy ofE. histolytica and developed PCR-based methods for distinguishing field isolates of E. histolytica or E. dispar. Fluorescence in situ hybridization showed that E. histolytica trophozoites are diploid for five “single-copy” probes tested. Intergenic sequences between superoxide dismutase an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(20 citation statements)
references
References 45 publications
2
18
0
Order By: Relevance
“…However, the Ehcht gene sequence obtained in the right hepatic lobule abscess is identical to the one on NIH-200 and K1 E. histolytica strains reported by Ghosh and others. 4 Translation of the nucleotide sequences into amino acid sequences and the corresponding alignment is shown in Figure 2B and correlates with the nucleotide sequences mentioned earlier.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…However, the Ehcht gene sequence obtained in the right hepatic lobule abscess is identical to the one on NIH-200 and K1 E. histolytica strains reported by Ghosh and others. 4 Translation of the nucleotide sequences into amino acid sequences and the corresponding alignment is shown in Figure 2B and correlates with the nucleotide sequences mentioned earlier.…”
Section: Resultssupporting
confidence: 75%
“…The high rate of intestinal re-infection in highly endemic areas is mainly the result of repetitive exposure to Entamoeba parasites. [3][4][5][6][7][8] The development of repeated ALA is more frequent than previously thought. [9][10][11] Furthermore, it has been reported that roughly 50% of ALA cases develop more than one ALA at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…These polymorphic loci are potentially useful in the molecular epidemiology of amebiasis. 35,39 Preliminary data concerning the polymorphism of serine-rich protein and chitinase loci of E. histolytica and E. dispar in isolates obtained from patients with invasive amoebiasis and from asymptomatic cyst passers from different geographic areas in Mexico suggested a complex geographic distribution of different strains of both Entamoeba species. 40 However, no correlation was found between a particular polymorphic pattern of a given E. histolytica isolate and the invasive or commensal behavior within the human host.…”
Section: Discussionmentioning
confidence: 99%
“…The amoebic Ser-rich protein gene repeats were amplified using PCR and primers specific for E. histolytica. An E. histolytica Ser-rich protein-specific sense primer was GCTAGTCCTGAAAAGCTTGAAGAAGCTG (Primer1), while an E. histolytica Ser-rich proteinspecific antisense primer was GGACTTGATGCAGCATCAAGGT (12). The procedure was as follows: all solutions were gently vortexed and briefly centrifuged after thawing.…”
Section: Pcr Amplification Of Ser-rich Entamoeba Histolytica Protein mentioning
confidence: 99%